2013
DOI: 10.2147/ndt.s40213
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatal and nonfatal repetition of suicide attempts: a literature review

Abstract: ObjectivesThis review aimed to identify the evidence for predictors of repetition of suicide attempts, and more specifically for subsequent completed suicide.MethodsWe conducted a literature search of PubMed and Embase between January 1, 1991 and December 31, 2009, and we excluded studies investigating only special populations (eg, male and female only, children and adolescents, elderly, a specific psychiatric disorder) and studies with sample size fewer than 50 patients.ResultsThe strongest predictor of a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 81 publications
9
60
4
5
Order By: Relevance
“…Despite the fact that some studies have shown more ideation, planning, and attempts among young people -especially the latter (e.g., Nkansah-Amankra, 2013; ten Have et al, 2013) -, other studies find higher rates of suicide in these people (e.g., Cano et al, 2012;Vougiouklakis, Tsiligianni, & Boumba, 2009). It seems that suicide ideation and attempts tend to appear in young adults, increasing the risk of suicide after puberty (Beautrais et al, 2005;Gisle & Van Hoye, 2013;Ministerio de Sanidad, Política Social e Igualdad, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the fact that some studies have shown more ideation, planning, and attempts among young people -especially the latter (e.g., Nkansah-Amankra, 2013; ten Have et al, 2013) -, other studies find higher rates of suicide in these people (e.g., Cano et al, 2012;Vougiouklakis, Tsiligianni, & Boumba, 2009). It seems that suicide ideation and attempts tend to appear in young adults, increasing the risk of suicide after puberty (Beautrais et al, 2005;Gisle & Van Hoye, 2013;Ministerio de Sanidad, Política Social e Igualdad, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Igualdad, 2012). Moreover, due to the increase of life expectancy and a greater accessibility to health services, the population seem to grow older showing a higher number of old adults, implying a rise in the rates of this group and making them more noticeable than the ones of the young people (Beautrais, Collings, Ehrhardt, & Henare, 2005). Despite the fact that some studies have shown more ideation, planning, and attempts among young people -especially the latter (e.g., Nkansah-Amankra, 2013; ten Have et al, 2013) -, other studies find higher rates of suicide in these people (e.g., Cano et al, 2012;Vougiouklakis, Tsiligianni, & Boumba, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sexual trauma is a risk factor for repeated suicide attempts. 30 Examination of mental health quality indicators such as treatment intensity and continuity of care, which may influence suicide risks, 31 is also important for further research regarding MST-related mental health treatment. However, because MST exerted a significant independent effect on suicide mortality that was not accounted for by medical or mental health conditions, sexual trauma should be considered in suicide prevention strategies, even among individuals without documented psychiatric morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 29 studies in this overview, however, only 12 mentioned such an exclusion criterion, although all investigators may have tried to exclude suicidal patients to limit liability. What seems even more important is that, unfortunately, suicides and suicide attempts are exceedingly difficult to predict [12,13,14,15]. Hence, even the exclusion of patients considered to be at risk is unlikely to result in substantial risk reductions for samples as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…This disadvantage seems especially relevant for suicide and suicide attempts. The complexity of this behavior is illustrated by the difficulties in predicting suicides and suicide attempts with sufficient certainty - despite a host of risk factors that have been published [12,13,14,15]. For an overview of methodological difficulties in suicide research, see the study by de Leon et al [16].…”
Section: Introductionmentioning
confidence: 99%